2013
DOI: 10.1002/14651858.cd008090.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Larvivorous fish for preventing malaria transmission

Abstract: Background Adult anopheline mosquitoes transmit Plasmodium parasites that cause malaria. Some fish species eat mosquito larvae and pupae. In disease control policy documents, the World Health Organization includes biological control of malaria vectors by stocking ponds, rivers, and water collections near where people live with larvivorous fish to reduce Plasmodium parasite transmission. The Global Fund finances larvivorous fish programmes in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 60 publications
0
38
0
1
Order By: Relevance
“…In a step-wedge study, the intervention is rolled out randomly to clusters in a staged fashion so that by the end of the study all clusters will have received the intervention. Adapted from [32].…”
Section: Keymentioning
confidence: 99%
See 1 more Smart Citation
“…In a step-wedge study, the intervention is rolled out randomly to clusters in a staged fashion so that by the end of the study all clusters will have received the intervention. Adapted from [32].…”
Section: Keymentioning
confidence: 99%
“…To date, however, many Phase III studies often focus exclusively on entomological outcomes, which are generally useful only for demonstrating proof of concept or as a secondary outcome in support of an epidemiological primary outcome. For example, a Cochrane systematic review on larvivorous fish for malaria control did not identify any studies with epidemiological outcomes [32]. The best epidemiological measure is the incidence of clinical disease or disease-specific mortality, but for some diseases, such as dengue, seroincidence (seroconversion in sequential blood draws) and the prevalence of infection in .…”
Section: Reviewmentioning
confidence: 99%
“…Trends in malaria transmission and performance of VCTs are also confounded by longer-term changes in environmental and infrastructural landscapes and climate (Snow et al, 2017). Although Cochrane reviews remain the gold standard in evidence-based policy, it is often inappropriate to combine findings from studies across different eco-epidemiological settings when VCT efficacy is tied to local transmission ecology (Walshe et al, 2013;Tusting et al, 2013). Second, some emerging VCTs remain years away from accumulating a full dossier of epidemiological evidence, and although further Phase III studies are planned (Thomas M et al, 2015), nearing completion (Mtove et al, 2016), or recently concluded (Homan et al, 2017), we identified fourteen VCTs for which no Phase III epidemiological data were available within the search dates.…”
Section: Discussionmentioning
confidence: 99%
“…Larval source management (LSM): A Cochrane review compared biological control with larvivorous fish to biological control without larvivorous fish (Walshe et al, 2013). No eligible studies included in this review measured malaria incidence, entomological inoculation rate (EIR), or adult vector density (Table 3).…”
Section: Vcts With a Recent Systematic Reviewmentioning
confidence: 99%
“…and Poecilia reticulate could potentially be released in the large water-storage jars close to tappers' houses. Although a recent systematic review found that there was a lack of evidence that fish were effective control agents [84], additional well-conducted studies are needed before a recommendation can be made. Other examples of natural predators include the entomophilic mermithid nematode Romanomermis iyengari and the naturally occurring predatory mosquito Toxorhynchites splendens, which have been effective at reducing Ae.…”
Section: Larval Source Management (Lsm)mentioning
confidence: 99%